Single dose of 300 IU hCG in the early luteal phase in superovulated ewes: Effects on corpora lutea, progesterone profile, and embryo recovery - Dias, J. H.; Gonçalves, J. D. [UNESP]; Arrais, A. M.; Batista, R. I.T.P.; Souza-Fabjan, J. M.G.; Bastos, R.; Siqueira, L. G.B.; Oliveira, M. E.F. [UNESP]; Fonseca, J. F. (Elsevier, 2022)
This study aimed to evaluate the effects of hCG treatment during the early luteal phase on ovarian function, progesterone profile, and embryo yield in superovulated ewes. Superovulated sheep were randomly assigned to receive 300 IU hCG i.m. (GhCG, n = 24) or not (GControl, n = 25) at 96 h after the removal of the progesterone (P4) device (D13). Non-surgical embryo recovery (NSER) was performed eight days after P4 withdrawal. Ultrasound evaluations were performed on D13, D14, D16, and D17. Blood samples were collected on D14, D16, and D17. Superovulation scores were recorded based on the number of corpora lutea (CL) as follows: 1 (≤ 2), 2 (3−5), 3 (6−8), and 4 (≥ 9). NSER efficiency, superovulation response, and luteal tissue area were similar in both groups (P > 0.05). Structural luteolysis tended to be higher in GControl (P = 0.07; 47.0 %) while functional luteolysis was similar in both groups (P > 0.05; 0.0 % and 5.9 %). The recovery rate was greater (P < 0.05) in GhCG (89.8 %) compared with GControl (71.0 %), with similar overall ova/embryo numbers observed for both groups (P > 0.05). GhCG showed a higher concentration of animals with a superovulatory response score of 4 (54.5 %; P < 0.05) compared with the lowest scores. Plasma progesterone on D16 was higher (P < 0.05) in GhCG ewes (11.1 ± 1.5 vs 6.9 ± 1.5 ng/mL). In conclusion, the hCG treatment improved circulating P4 and embryo recovery rate, tended to maintain luteal functionality, and thus constitutes an additional tool for improving embryo yield in superovulated ewes.
Keywords: Corpus luteum; Embryo; NSER; Ovine; Superovulation